COLLEGE STUDENTS’ PERCEPTIONS ON THE USE OF ORAL PRESENTATION AS A TEACHING AND LEARNING TECHNIQUE IN THE CLASSROOM - Ismail Petrus (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: Task-based learning has generally been implemented for university students. One task type common to especially language students is oral presentation. Giving an oral presentation may seem to be a limited activity, but it actually involves all the language skills. The students should read and write in the preparation, speak in the presentation, and listen and speak in response to questions. This paper presents a study of the students’ perceptions on the use of oral presentation as a teaching and learning technique in the classroom. The participants of the study were 120 undergraduate English Education students of two different courses. The data were collected mainly from the students’ essays, written at the end of semester, on the advantages and disadvantages of using the technique in the classroom. The data were then analyzed both quantitatively and qualitatively. The quantitative analysis was first used for assessing the responses obtained from the essays; and secondly, the qualitative analysis provided the evaluation and interpretation of the figures. The results showed that most students appreciated the use of oral presentation in the classroom because the technique would make them become more responsible and active in their own learning; however, some less-motivated students would focus only on the materials in their own presentations and would not pay enough attention to other students’ presentations. Key words: task, teaching and learning technique, oral presentation